2000
DOI: 10.1002/1521-4141(200003)30:3<778::aid-immu778>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Thymosin-α1 regulates MHC class I expression in FRTL-5 cells at transcriptional level

Abstract: In this study we examined the effect of the synthetic peptide thymosin‐α1 (Tα1) on MHC class I expression in FRTL‐5 cells. Treatment with Tα1 increased expression of MHC class I surface molecules and mRNA, which reached its peak (153 ± 8 % of the control value) after 12 h. Chloramphenicol acetyltransferase (CAT) analysis, following transfection with a plasmid containing the regulatory sequence of MHC class I (or its deletion derivatives) with the CAT reporter gene, and electrophoretic mobility shift assay expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
62
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(63 citation statements)
references
References 28 publications
1
62
0
Order By: Relevance
“…Since 1994, ProTα has been reported to inhibit the replication of virus and the reproduction of cancer cells by inducing immune cells (Baxevanis et al, 1994(Baxevanis et al, , 1995Haritos et al, 1985;Romani et al, 2004). Thymosin α1, corresponding to the first 28 amino acid residues of ProTα, was reported to increase the expression of MHC I which presented endogenous peptides to cytotoxic T cells to kill the virally infected cells as well as some cancer cells (Giuliani et al, 2000). It was also reported that Thymosin α1 inhibited viral replication in hepatitis virus B-transfected HepG2 tumor cells (Moshier et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Since 1994, ProTα has been reported to inhibit the replication of virus and the reproduction of cancer cells by inducing immune cells (Baxevanis et al, 1994(Baxevanis et al, , 1995Haritos et al, 1985;Romani et al, 2004). Thymosin α1, corresponding to the first 28 amino acid residues of ProTα, was reported to increase the expression of MHC I which presented endogenous peptides to cytotoxic T cells to kill the virally infected cells as well as some cancer cells (Giuliani et al, 2000). It was also reported that Thymosin α1 inhibited viral replication in hepatitis virus B-transfected HepG2 tumor cells (Moshier et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, there is an increased expression of MHC class I and II molecules in pancreatic islet cells of patients with type 1 diabetes mellitus and in thyrocytes from patients with autoimmune thyroid diseases (Hanafusa et al 1983, Bottazzo et al 1985, Kohn et al 2000. The importance of MHC class I overexpression is suggested by the observation that MHC class I-deficient mice do not develop autoimmunity in different experimental models: systemic lupus erythematosus (SLE), diabetes and autoimmune blepharitis (Mozes et al 1993, Serreze et al 1994, Chan et al 1995, Singer et al 1999.…”
Section: Introductionmentioning
confidence: 99%
“…We hypothesized that hormonal suppression of class I levels might be a physiologic mechanism to preserve self-tolerance and prevent autoimmune thyroid disease in the face of the hormonal increase of thyroid-specific genes, which are potential autoantigens (Saji et al 1992a, 1992b, 1997, Giuliani et al 1995, Taniguchi et al 1998, Kohn et al 2000. Other growth factors and cytokines, such as transforming growth factor (TGF)-1, thymosin 1 and , -interferons, also regulate MHC class I expressions in thyroid cells (Saji et al 1992b, Grassadonia et al 2004.…”
Section: Introductionmentioning
confidence: 99%
“…Ta1 has also been shown to increase expression of proteins on the surface of virally-infected or tumor cells, including those that mediate antigen presentation such as Major Histocompatibility (MHC) Class I, MHC Class II, and beta-2 microglobulin [36,63], as well as tumorspecific antigens [64,65]. Immune escape by virally-infected and tumor cells has been correlated with down-regulation of antigen-presenting molecules [66,67].…”
Section: Direct-acting Effectsmentioning
confidence: 99%